Bharatanatyam as a Transnational and Translocal Connection: A Study of Selected Indian and American Texts - Kang, Manpreet Kaur (Review of International American Studies, 2020)
Bharatanatyam is a classical dance form derived from ancient dance styles, which is now seen as representative of Indian culture. In India, it is the most popular classical dance form exerting a great impact not only on the field of dance itself, but also on other art forms, like sculpture or painting. The Indian-American diaspora practices it both in an attempt to preserve its culture and as an assertion of its cultural identity. Dance is an art form that relates to sequences of body movements that are simultaneously aesthetic and symbolic, and rooted in specific cultures. It often tells a story. Different cultures observe different norms and standards by which dances should be performed (as well as by whom they should be performed and on what occasions). At the same time, dance and dancers influence (and are influenced by) different cultures as a result of transcultural interactions. Priya Srinivasan’s Sweating Saris: Indian Dance as Transnational Labor is a particularly valuable source wherein its author critically examines a variety of Indian dance forms, especially Bharatanatyam, tracing the history of dance as well as the lived experience of dancers across time, class, gender, and culture. With the help of this text, selected journal articles, and interviews with Bharatanatyam dancers in India and the US, I explore larger issues of gender, identity, culture, race, region, nation, and power dynamics inherent in the practice of Bharatanatyam, focusing on how these practices influence and, in turn, are influenced by transnational and translocal connections.